Conceptualisation of music by metaphors of space and movement - Mikalonytė, Elzė Sigutė; Dranseika, Vilius (Psichologija, 2018)
The usage of metaphors of space and movement is a common way to conceptualize what is heard in music. However, there are not many empirical studies that investigate this process, and almost all of them were conducted using extremely simple stimuli. The aim of this study is to understand how specific the connection between the properties of musical sound and the concepts of space and movement is, and to check if musical education has any influence on this process. We conducted two studies wherein excerpts from real instrumental classical music recordings were used. Study participants listened to a number of excerpts from instrumental classical music recordings and – after each excerpt – the participants were asked to rate how appropriate different concepts were for describing the excerpts. Six concepts were used in the first study on synesthetic metaphors: rising, falling, widening, narrowing, approaching, moving away (the last two were used as controls). In the second study, we used concepts that are transferred to music from normal auditory cognition. Namely, participants were asked to rate the appropriateness of six concepts (approaching, moving away, gaining energy, losing energy, accelerating, slowing down). The results of these two studies show that even if the simplest concepts of space and movement are chosen, there is no “one-to-one” connection between the properties of sound and the concepts used to describe them; however, a number of regularities were observed. Moreover, associations between the properties of sound and the concepts of space and movement were symmetrical. This means that if one property of sound is associated with a concept, then an opposite property is associated with an opposite concept, but only if the concepts that are theoretically predicted to be chosen are considered. The studies also did not observe any important differences between study participants with musical education and those without musical education.